2017
DOI: 10.1007/s10195-017-0457-8
|View full text |Cite
|
Sign up to set email alerts
|

Failure and revision rates of proximal humeral fracture treatment with the use of a standardized treatment algorithm at a level-1 trauma center

Abstract: BackgroundThe aims of this study were to evaluate treatment failure and revision rates of proximal humeral fracture (PHF) treatment with a standardized treatment algorithm within the reality of a level-1 trauma center and to identify predictors of subsequent surgery.Materials and methodsThe medical database of a level-1 trauma center was screened for all primary treatments of PHFs between January 2009 and June 2012. Medical records and imaging were analyzed to identify the fracture morphology, pre-existing dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
1
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 42 publications
2
10
1
5
Order By: Relevance
“…Despite identification of several potential risk factors for fixation failure and regardless of the continuous development of implants with improved plate and screw design, the complication rate associated with locked plating of PHF is still high [ 2 , 7 , 8 ]. Especially in fragility fractures of the older population, loss of reduction with secondary articular screw perforation and varus displacement with loss of fixation can still be observed in up to 20% of cases within the first 12 months postoperatively [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite identification of several potential risk factors for fixation failure and regardless of the continuous development of implants with improved plate and screw design, the complication rate associated with locked plating of PHF is still high [ 2 , 7 , 8 ]. Especially in fragility fractures of the older population, loss of reduction with secondary articular screw perforation and varus displacement with loss of fixation can still be observed in up to 20% of cases within the first 12 months postoperatively [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Plate fixation for comminuted PHF poses a surgical challenge [ 5 ]. Even when anatomical reduction of the deformity with reconstruction of the humeral head is initially accomplished, a high risk for early and late complications can compromise the final outcome [ 23 , 24 ]. To overcome the mechanical limitations of plate fixation in the setting of poor bone biology and complex fractures, compensating for lack of structural integrity is mandatory.…”
Section: Discussionmentioning
confidence: 99%
“…In the treatment algorithm proposed by Katthagen et al, it was suggested that no attempt at locking plate reconstruction need be undertaken in the context of severe comminuted fractures in patients older than age 60 years [ 23 ]. The authors favor a shoulder hemiprosthesis in such patients.…”
Section: Discussionmentioning
confidence: 99%
“…Based on results of endoprosthetics following fractures of the proximal humerus, the correction osteosynthesis indeed represents a real therapeutic alternative in patients that are below the age of 60, a good bone mass and with relative functional requirements. Im eigenen Patientengut wurden von 2009 bis 2012 423 von 566 Patienten (75 %) mit einem durchschnittlichen Alter von 68,3 ± 13,9 Jahren telefonisch kontaktiert und nach erneuter/weiterer Behandlung nach proximaler Humerusfraktur befragt [5].…”
Section: Introductionunclassified
“…Bei einem Follow-up von 23,4 Monaten wurde bei 94 Fällen (22,2 %) eine erneute/erstmalige operative Behandlung durchgeführt [5]. Bei 39 Patienten (9,2 %) zeigte sich ein Therapieversagen im Sinne von ▪ sekundärer OP nach konservativer Therapie, ▪ Verfahrenswechsel, ▪ sekundärem Gelenkersatz.…”
Section: Introductionunclassified